Convergência das normas brasileiras de contabilidade do setor público às normas internacionais de contabilidade do setor público: um ensaio teórico - Sousa, Heloísa Viana de (2011)
Accounting works in the generation of information to all users based on its own methodology, and to achieve its goal is influenced by information and communication technologies and also by the process of social, economic and institutional development. At the current moment of evolution of science accounting, it has been subject to discussions on the development of standards and rules that promote convergence based on international accounting standards. In this context, the main purpose of this study was to analyze the convergence between Brazilian standards and international accounting standards applied to public sector starting with the comparative analysis of the Brazilian Accounting Standards to Public Sector (NBC T SP) and International Public Sector Accounting Standards (IPSAS), issued by the end of 2010.